2015
DOI: 10.1073/pnas.1513045112
|View full text |Cite
|
Sign up to set email alerts
|

HSV targeting of the host phosphatase PP1α is required for disseminated disease in the neonate and contributes to pathogenesis in the brain

Abstract: Newborns are significantly more susceptible to severe disease after infection with herpes simplex virus (HSV) compared with adults, with differences in the host response implicated as a major factor. To understand host response differences between these age groups, we investigated the shutoff of protein synthesis by the host and the retargeting of host phosphatase PP1α by the HSV-1 protein γ34.5 for reversal of translational arrest. In a murine newborn model of viral dissemination, infection with the HSV-1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…To evade this, HSV-1 ␥ 1 34.5 recruits cellular phosphatase 1 (PP1), forming a high-molecular-weight complex that dephosphorylates eIF-2␣ (21)(22)(23). Accordingly, mutations in the PP1 binding site abrogate viral virulence (24,25). The ␥ 1 34.5 protein also inhibits autophagy, IFN induction, and dendritic cell maturation and facilitates glycoprotein processing as well as nuclear egress (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…To evade this, HSV-1 ␥ 1 34.5 recruits cellular phosphatase 1 (PP1), forming a high-molecular-weight complex that dephosphorylates eIF-2␣ (21)(22)(23). Accordingly, mutations in the PP1 binding site abrogate viral virulence (24,25). The ␥ 1 34.5 protein also inhibits autophagy, IFN induction, and dendritic cell maturation and facilitates glycoprotein processing as well as nuclear egress (6,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…. The IFNAR and PKR, two components previously shown to be important to control HSV infection in the brain (Leib et al, 2000;Wilcox et al, 2015a), were found to have 4-to 6-fold higher levels of basal expression in the adult, while other components such as STAT1, TBK1, cGAS, and TLR3 were present in lower levels in the adult brain. Interestingly, STING, another important component of the innate immune response to HSV in the brain (Parker et al, 2015), is present at similar levels in newborn and adult brains.…”
Section: Newborn Susceptibility To Hsv-1 Infectionmentioning
confidence: 84%
“…It also targets TLR signaling by promoting degradation of adaptor proteins MyD88 and Mal. The immediate early protein ICP27 targets the NF-kB and IRF-3 signaling pathways (Kim et al, 2008); g34.5, another major virulence factor, targets several pathways to counteract the host IFN response Roizman, 1992, 1994); g34.5 mediates the dephosphorylation of eIF2a and IKKa to reverse host shutoff of protein synthesis (He et al, 1997;Wilcox et al, 2015a), inhibits TBK1 to prevent activation of the type I IFN response (Verpooten et al, 2009), and binds to beclin-1 to inhibit autophagy (Orvedahl et al, 2007;Gobeil and Leib, 2012). The multiple strategies developed by the virus to neutralize the host type I IFN response strongly support the essential role of this pathway in controlling HSV infection .…”
Section: Hsv-1 and The Type I Ifn Responsementioning
confidence: 99%
“…As indicated above, HSV-1 γ34.5 recruits phosphatase PP1α to reverse eIF2α-mediated translational arrest. It has been reported that PP1α contributes to HSV-1 pathogenesis and is required for disseminated disease in the brain 39 . To address whether NOP53 relates functionally with PP1α, okadaic acid (OA) was used to induce eIF2α phosphorylation in this study.…”
Section: Nop53 Attenuates the Phosphorylation Level Of Endogenous Andmentioning
confidence: 99%